Morpho-chemical quality improvement in tomato (Solanum lycopersicum) through heterosis breeding - SINGH, ASHISH K; SOLANKEY, S S; KUMARI, MEENAKSHI; SINGH, NEERAJ (The Indian Journal of Agricultural Sciences, 2019)
The demand of tomato (Solanum lycopersicum L.) and its products continue to rise due to its excellent source of antioxidants including lycopene, total carotenoids, ascorbic acid and total soluble solids. The present experiment was carried out during the autumn-winter season of 2014–2016. The seven parents were crossed in half diallel fashion and the resultant 21 F1 hybrids along with their parents and one hybrid check (BSS - 488) were evaluated in randomized complete block design with three replications for eight morpho-chemical quality component traits in tomato. The highest standard heterosis were observed in the cross Selection-12 × Pusa-120 (12.16%) for pericarp thickness, Pusa Rohini × Selection-12 (25.95%) for total soluble solids, H-86 × Pusa Rohini (23.53) for ascorbic acid, Selection-12 × CLNB (38.79) for total phenolics, Arka Alok × CLNB (46.49) for total antioxidant capacity, Pusa Rohini × Arka Alok (25.95) for lycopene and total carotenoids (29.53). Among the crosses Pusa Rohini × CLNR, Arka Alok × CLNB, H-86 × Pusa-120 and H-86 × CLNR were found to be better for most of the quality traits and these crosses could be considered as most promising specific combiners. Among the parents, Selection-12, CLNB, Pusa Rohini and Arka Alok were identified as most promising general combiners for quality traits and these may be used as valuable donors in the hybridization programme for producing promising varieties.